(untitled) (De Musica, 2025)
Béla Bartók’s music never fails to seduce, even a century later. His extremely curios mind led him to explore the Hungarian countryside collecting folk music: from asymmetrical meters to modality, he was deeply permeated by its non-conventional traits, also offering a fundamental lesson to the new-born Ethnomusicology. Besides, the Hungarian composer had a strong interest in nature’s inner voice, which he tried to put on paper investigating its mathematical principles. In so doing, he shaped a very original aesthetics of music, and he would have rigorously complied with it for the rest of his life. This paper aims to investigate the most relevant characteristics of Bartók’s musical language in order to highlight its ultimate meaning, which could be possibly summarised as a “return to the origins”. Music for strings, percussions and celesta, an incredibly innovative work first performed in 1937, exemplifies Bartók’s unique poetics, with striking similarities to that of the contemporary painter Piet Mondrian. The most remarkable feature of this masterpiece is that proportions form arithmetical patterns consistently recurring both as a whole and in detail. In light of these considerations, Bartók’s use of Golden ratio, a topic which is still very controversial, may find a plausible interpretation.